2019
DOI: 10.1073/pnas.1911252116
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial transcription factor A promotes DNA strand cleavage at abasic sites

Abstract: In higher eukaryotic cells, mitochondria are essential subcellular organelles for energy production, cell signaling, and the biosynthesis of biomolecules. The mitochondrial DNA (mtDNA) genome is indispensable for mitochondrial function because it encodes protein subunits of the electron transport chain and a full set of transfer and ribosomal RNAs. MtDNA degradation has emerged as an essential quality control measure to maintain mtDNA and to cope with mtDNA damage resulting from endogenous and environmental fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 68 publications
(97 reference statements)
2
47
0
Order By: Relevance
“…APE1 is known to localize to mitochondria and particularly relevant to AP lesion repair. We found that TFAM competes actively with APE1-mediated DNA cleavage using mitochondrial extracts from HeLa and HEK-293 cells [162], suggesting that TFAM interacts strongly with AP lesions under physiological concentration ratios of TFAM to APE1, and TFAM could play a regulatory role in mtDNA repair, as suggested previously [161]. Because mtDNA degradation and repair may occur in parallel to alleviate abasic DNA damage [127], it is plausible that TFAM could act redundantly with APE1 to trigger mtDNA turnover or to regulate the partitioning between mtDNA degradation and repair.…”
Section: Tfammentioning
confidence: 90%
See 2 more Smart Citations
“…APE1 is known to localize to mitochondria and particularly relevant to AP lesion repair. We found that TFAM competes actively with APE1-mediated DNA cleavage using mitochondrial extracts from HeLa and HEK-293 cells [162], suggesting that TFAM interacts strongly with AP lesions under physiological concentration ratios of TFAM to APE1, and TFAM could play a regulatory role in mtDNA repair, as suggested previously [161]. Because mtDNA degradation and repair may occur in parallel to alleviate abasic DNA damage [127], it is plausible that TFAM could act redundantly with APE1 to trigger mtDNA turnover or to regulate the partitioning between mtDNA degradation and repair.…”
Section: Tfammentioning
confidence: 90%
“…Furthermore, TFAM has been proposed to play a role in regulating mtDNA repair [161], though the underlying mechanism remains to be clarified. Recently, my laboratory has identified a novel role for TFAM in facilitating the degradation of damaged mtDNA containing abasic (AP) sites [162], which are ubiquitous DNA lesions and an important intermediate during BER.…”
Section: Tfammentioning
confidence: 99%
See 1 more Smart Citation
“…The selective depletion of damaged mtDNA lowers the overall population of mutated and/or deleted mtDNA molecules. For example, mtDNA molecules harboring abasic sites ( 77 , 78 ) or DNA double-stranded breaks (DSBs) ( 72 , 73 ) could be directly degraded rather than repaired. As mtDNA is under a strict copy-number control, selective depletion of damaged mtDNA molecules triggers replication of the undamaged mtDNA copies, reconstituting the mtDNA pool (reviewed in ( 79 )).…”
Section: Mitochondrial Dna Repair and Deletion Formationmentioning
confidence: 99%
“…Among the proteins that negatively regulate BER, TFAM binds the damaged mtDNA in close proximity to an abasic site. By steric exclusion of BER proteins, such as glycosylases and the APE1 nuclease, TFAM inhibits BER activation and promotes the degradation of the targeted mtDNA molecule ( 77 , 78 ). In stark contrast with its established roles in promoting nuclear DNA repair, the PARP1 protein inhibits BER within mitochondria.…”
Section: Base Excision Repair Is a Bona Fide Repair Pathway In The MImentioning
confidence: 99%